2023
DOI: 10.1021/acsami.2c23278
|View full text |Cite
|
Sign up to set email alerts
|

Toward Narrowband and Efficient Blue Fluophosphors by Locking the Stretching Vibration of Indolocarbazole Skeletons

Abstract: Developing efficient and color-saturated deep-blue emitting molecules with small Commission Internationale de L’Eclairage (CIE) y values is challenging and has great potential for wide-color gamut displays. Herein, we introduce an intramolecular locking strategy to restrain molecular stretching vibrations of the emission spectral broadening. By cyclizing rigid fluorenes and connecting electron-donating groups to the indolo[3,2,1-jk]-indolo[1′,2′,3′:1,7]indolo[2,3-b]carbazole (DIDCz) framework, the in-plane swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…pICz-Br was synthesized according to a reported method, 42 and then reacted with diphenyl(4-(4,4,5,5tetramethyl-1,3,2-dioxaborolan-2-yl)phenyl)phosphine oxide of different stoichiometric proportions to synthesize the targeted products pICz-PPO and pICz-2PPO by the Suzuki-Miyaura coupling reaction. The two emitters were characterized by 1 H/ 13 C NMR spectroscopy and mass spectrometry. The thermal properties were investigated by TGA measurements.…”
Section: Molecular Design and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…pICz-Br was synthesized according to a reported method, 42 and then reacted with diphenyl(4-(4,4,5,5tetramethyl-1,3,2-dioxaborolan-2-yl)phenyl)phosphine oxide of different stoichiometric proportions to synthesize the targeted products pICz-PPO and pICz-2PPO by the Suzuki-Miyaura coupling reaction. The two emitters were characterized by 1 H/ 13 C NMR spectroscopy and mass spectrometry. The thermal properties were investigated by TGA measurements.…”
Section: Molecular Design and Synthesismentioning
confidence: 99%
“…2–4 Therefore, the development of pure deep-blue emitters with narrowband emission and high efficiency is increasingly prevalent due to their good potential to reduce power consumption and realize wide color gamut for UHD displays. 5–13 Recently, multiple-resonance (MR) organic emitters have emerged as promising candidates to overcome the drawbacks of conventional OLEDs driven by their efficient narrowband emission character. 14–28 By integrating an opposite resonance effect of the electron-donating unit and the electron-withdrawing unit in a fused polycyclic framework, the MR effect could be triggered, which minimizes the bonding/antibonding character and suppresses the vibronic coupling between the ground (S 0 ) and the lowest excited singlet (S 1 ) states, giving rise to guaranteed sharpened spectra.…”
Section: Introductionmentioning
confidence: 99%
“…also developed the first narrowband BODIPY‐based OLED matching the pure red standard defined by National Television Standards Committee (NTSC) with EQE of 18.3 % peaked at 623 nm. Recently, pioneered by Lee et al., [3a] a series of ICz derivatives with small FWHMs near 20 nm were constructed to fabricate narrowband OLEDs, but the emission peaks are mostly located at violet‐to‐blue region due to the neglectable charge‐transfer (CT) property [3b–g] . Duan et al.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, a new type of nitrogen-embedded MR framework for OLED application was developed by fusing two or more indolo­[3,2,1- jk ] carbazole (ICz) units, in which each N-centered tripod structure is surrounded by three aromatic rings. Lee and co-workers first reported a pure violet emitter (named tDIDCz) by fusing two ICz units together, which exhibits exceptionally high color purity (fwhm <20 at 393 nm center wavelength) .…”
mentioning
confidence: 99%
“…Besides external effects, such as environmental heterogeneity and microcavity, the color purity of OLED emitters is generally determined by structural rigidity and vibronic coupling . The rigidity represents structural relaxation of S 1 → S 0 transition and determines fundamental broadening of emission spectra, while vibronic coupling, i.e., frequency and coupling strength (Huang–Rhys factor) of dominated vibrational modes, determines the vibronic progression. ,,, For instance, high color purity of B–N MR emitters was attributed to dominance of the low-frequency mode (e.g., framework bending, usually <50 cm –1 ) in vibronic coupling, while recent investigation indicated that structural rigidity of B–N frameworks is actually lower than expected. , As mentioned above, the color purity of ICz-based MR emitters is highly dependent on the linking-manner of frameworks, for which we further explored S 1 /S 0 structural relaxation and vibronic coupling quantitatively and tried to find the key factor that determines the emitting color purity of ICz-based MR emitters.…”
mentioning
confidence: 99%